Intraclonal Variations Among Streptococcus pneumoniae Isolates Influence the Likelihood of Invasive Disease in Children - Browall, Sarah (Oxford University Press, 2014)
Background. Pneumococcal serotypes are represented by a varying number of clonal lineages with different genetic contents, potentially affecting invasiveness. However, genetic variation within the same genetic lineage may be larger than anticipated. Methods. A total of 715 invasive and carriage isolates from children in the same region and during the same period were compared using pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing. Bacterial genome sequencing, functional assays, and in vivo virulence mice studies were performed. Results. Clonal types of the same serotype but also intraclonal variants within clonal complexes (CCs) showed differences in invasive-disease potential. CC138, a common CC, was divided into several PFGE patterns, partly explained by number, location, and type of temperate bacteriophages. Whole-genome sequencing of 4 CC138 isolates representing PFGE clones with different invasive-disease potentials revealed intraclonal sequence variations of the virulence-associated proteins pneumococcal surface protein A (PspA) and pneumococcal choline-binding protein C (PspC). A carrier isolate lacking PcpA exhibited decreased virulence in mice, and there was a differential binding of human factor H, depending on invasiveness. Conclusions. Pneumococcal clonal types but also intraclonal variants exhibited different invasive-disease potentials in children. Intraclonal variants, reflecting different prophage contents, showed differences in major surface antigens. This suggests ongoing immune selection, such as that due to PspC-mediated complement resistance through varied human factor H binding, that may affect invasiveness in children.